Overconfidence and Investment Decisions in Nepalese Stock Market - Shrestha, Niyam Raj (PYC Nepal Journal of Management, 2019)
This paper assesses the effect of overconfidence bias of an individual on investment decisions. This study uses the descriptive statistics and follows analytical approach to analyse the effects of investors’ behaviour on investment decisions. The data for the study were collected through questionnaire survey. This study finds that women investors, investors having college education, and investors having net worth between Rs 2 to 5 million are confident in their own ability. They believe that they are better investors than their peers and tend to trade more.